Numerical investigation of unsteady detonation waves in combustion chamber using Shchelkin spirals - Repaka Ramesh; C T Dheeraj Kumar Singh; Dr. Gurunadh Velidi (Carbon: Science and Technology, 2016)
: Pulse Detonation Engine (PDE) is considered to be a propulsive system of future air vehicles. The main objective is to minimizing the Deflagration to Detonation transition run-up distance and time by placing Shchelkin spiral with varying pitch length. Here we have considered blockage-area ratio is 0.5 as optimal value from review of previous studies. In the present study the detonation initiation and propagation is modeled numerically using commercial CFD codes GAMBIT and FLUENT. The unsteady and two-dimensional compressible Reynolds Averaged Navier-Stokes equation is used to simulate the model. Fuel-air mixture of Hydrogen-air is used for better efficiency of PDE. It is very simple straight tube with Shchelkin spirals, one of the methods which is used to initiate detonation is creation of high pressure and temperature chamber region with 0.5cm from closed end of tube where shock will generate and transition into low pressure and temperature region propagates towards end of the tube. Two different zones namely high and low pressure zones are used as interface in modeling and patching has been used to fill the zones with hydrogen and oxygen with different pressure and temperatures hence shock leads to propagate inside the combustion chamber.